All over the map: a backpacker's fantasy - Sethi, R S (New Delhi Vitasta Publishing, 2011)
On a trip to Oaxaca, Mexico, to celebrate her fortieth birthday, Laura Fraser confronts the unique trajectory of her life. Divorced and childless in her thirties, she found solace in the wanderlust that had always directed her heart--and found love and comfort in the arms of a dashing Frenchman. Their Italian affair brought her back to herself--but now she wonders if her passion for travel (and for short-lived romantic rendezvous) has deprived her of what she secretly wants most from life: a husband, a family, a home. When her Parisian lover meets her in Oaxaca and gives her news that he's found someone new, Laura is stunned and hurt.
Keywords: Description and Travel; IAS as an author